OVERVIEW AND IDEAS FOR ORGANIZING AN ONLINE LANGUAGE CLASS - Renita Donasari; Ossa Bodhi Tala; Nuriyatul Hamidah (Jurnal Bahasa Lingua Scientia, 2021)
Online language class can be set in two ways whether it uses a synchronous or asynchronous system. Due to the COVID-19 pandemic, the teaching-learning process is conducted online. Therefore, this paper does not only provide some overviews of the teaching-learning process in online English language classes (starting from providing an overview of the choices of a class setting, the tools and the reasons for their use, the challenges in conducting online language classes, the most applicable tools to use in online language classes) but also presents ideas covering four language skills to set online language classes in the post-pandemic era lively. This study uses convergent mixed method where questionnaires, interviews, and field notes are collected at roughly the same time to provide a comprehensive analysis of the research problem. The findings show a combination of synchronous and asynchronous learning as the most suitable and effective systems to conduct online language classes. The most challenging factors of online classes are adaptation in using an online learning platform and an unstable signal. WhatsApp and Google Classroom are the most used platform by the participants. In conclusion, combining both using synchronous and asynchronous learning is better to set creative audio-visual aid to deliver the lesson.